Picture of dorian gray - Wilde, Oscar (New Delhi : Fingerprint, 2023)
The soul is a Terrible reality. it can be bought And sold and bartered away.?Meet Dorian Gray, the beautiful young man with an impossibly charming face and spirit. as he sits for Basil Hallward?a deeply moral artist and a friend of the impish Lord Henry?who becomes obsessed with his beauty and wants to paint him, Dorian is enchanted by the perfection of his portrait.
Keywords: Fiction